Effectiveness of Kneading Technique on Joint Pain Among Old Age People with Osteoarthritis in Selected Old Age Homes at Bhubaneswar - Tiwari, Divyanshu; Sahoo, Ishita; Das, Minati (Journal of Neonatal Surgery, 2025)
This study aimed to evaluate the effectiveness of Kneading technique on joint pain among old-age people with Osteoarthritis in selected old age homes at Bhubaneswar Objective: To assess the level of joint pain among old age people with Osteoarthritis before and after the kneading technique, also aims to evaluate the effectiveness of kneading technique on level of joint pain among old age people with osteoarthritis. Method & Materials: The research design selected for this study was Quasi experimental pre test post test control group design. The investigator opted purposive sampling technique to select a sample of 40 (exprimental-20 and control-20) of old age people with osteoarthritis according to inclusion and exclusion criteria. Those who have no pain sensation, undergone surgery, handicapped or bedridden were excluded from the study. In this study self-structured socio-demographic data tool, Structured Visual analogue scale were used to measure and observe the study accurately. Data was analysed through descriptive and inferential statistics. Results: After the kneading technique it was remarked that in experimental group 30% samples had no pain, 45% samples had mild pain and 25% samples had moderate pain while in control group 30% samples had mild pain and 70% of the samples had moderate pain. It this study pre-test mean score and SD for the experimental group were 4.35±1.927, and for the post-test it reduced to 2.65±1.814. The difference between the pre-test and post-test mean scores and SD was 1.70 and ±0.801 respectively. It was found to be statistically significant (p<0.0001). In the control group, pre-test mean score and SD was 4.35 and ±1.785 respectively in post-test it reduced to 3.25±1.209. The difference in the score is 1.10±2.47. The paired t test value in experimental group is 9.488, in control group 1.993. It was found more than table value with at 0.05 level of significance. The difference was highly significant. Hence the hypothesis is rejected. Conclusion: This study revealed that Kneading technique was effective in reducing knee joint pain of old age people with osteoarthritis.